2016
DOI: 10.1037/ccp0000149
|View full text |Cite
|
Sign up to set email alerts
|

Change in patients’ interpersonal impacts as a mediator of the alliance-outcome association in treatment for chronic depression.

Abstract: Results further support CBASP change theory and suggest a candidate mechanism of the alliance's effect on outcome. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
2
17
1
1
Order By: Relevance
“…At the same time, low interpersonal hostility may make it easier for patients to collaborate with their therapist and to make use of their therapy. In previous research, a stronger alliance predicted reductions in patients' hostile-submissiveness, which in turn were related to improvements in depression (Constantino et al, 2016). Besides establishing a good alliance, the experience of agency might help to abandon maladaptive interpersonal ways of relating.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…At the same time, low interpersonal hostility may make it easier for patients to collaborate with their therapist and to make use of their therapy. In previous research, a stronger alliance predicted reductions in patients' hostile-submissiveness, which in turn were related to improvements in depression (Constantino et al, 2016). Besides establishing a good alliance, the experience of agency might help to abandon maladaptive interpersonal ways of relating.…”
Section: Discussionmentioning
confidence: 83%
“…In contrast, interpersonal change, which is, "stepping out" of maladaptive interpersonal cycles, would require therapists to limit their complementary reactions to their patients' interpersonal pulls and to gradually invite patients to move with more flexibility in the interpersonal space. This idea was supported by research from Constantino et al (2016) who showed that reductions in chronically depressed patients' hostile-submissiveness during therapy predict outcome. Further, the finding of the current study may be specific to the assessment of agency in an early therapy session and in the patients' subjective experience.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This model states that a novel relational experience in the therapeutic alliance is necessary for interpersonal change to occur and that this interpersonal change in turn leads to improvement of depression. To date, only one CBASP study supports this model [2]. It found an indirect effect of the alliance on outcome through patients' reduction in hostile submissiveness.…”
mentioning
confidence: 98%